Model Pembelajaran Pendidikan Agama Islam - Qomariyah, Nurul; Karoma, Karoma (Peneliti.net, 2025)
This study explores various instructional models within the context of Islamic Religious Education to enhance learning effectiveness and support curriculum innovation amid the demands of 21st-century education. Using a qualitative approach through library research, this study analyzes literature from books, journals, and credible academic sources that discuss relevant pedagogical frameworks. The findings reveal that instructional models such as social learning, distance learning, adult learning (andragogy), elaboration, skills-based learning, integrated learning, and project-based learning each offer distinct advantages. These models not only improve student engagement and critical thinking but also align with Islamic educational values and goals. By applying these models appropriately, educators can foster meaningful and transformative learning experiences. This study contributes to the discourse on Islamic pedagogy and underscores the importance of innovation and contextual teaching practices in responding to contemporary educational challenges.